Estudo de propriedades físico-químicas do etanol Hidratado com adição de biodiesel para uso em motores De combustão interna ciclo otto - Vanzella, Edson (2015)
The influence of the addition of biodiesel on hydrous ethanol for use at the internal combustion engines (Otto cycle), of vehicles and of aircrafts, as the utilized in the crop duster Ipanema, is that aimed to this study. The Brazilian Aeronautics Company - Embraer, in partnership with Aircraft Industry Neiva, Ipanema agricultural aircraft manufacturers, converted the engine of this aircraft, originally stocked with aviation gasoline (Avgas) for ethanol in 2005. The success of the conversion of the fossil fuel for the biofuel is proven and reported by aircraft operators throughout Brazil, with advantages environmental, economic, of infrastructure and yield. However, some physical and chemical properties of ethanol as the low lubricity, low flash point, its hygroscopic nature and low viscosity, may bring damage to components of the aircraft fuel system, as well as parts of the engine. Biodiesel possesses features that are useful to the Otto cycle engine, because its organic components associated with your higher electrical conductivity, provide high lubricity when it is added to the ethanol. Biodiesel flash point is high, and thus minimizes flammability risks from transport, storage and supply of ethanol. Because it is less corrosive than ethanol, biodiesel when mixed with ethanol also reduces the conditions of wear and corrosion on parts and engine parts. For diagnosing the ideals levels to the mixture formation were performed eight different compositions (four with soybean biodiesel and four with castor bean biodiesel) varying the percentage of biodiesel at 1%, 3%, 5% and 10% (m/m) in hydrous ethanol. Responses were observed in terms of calorific value, viscosity, flash point, density, electrical conductivity and turbidity for each blend. The calorific value and viscosity were influenced by the major carbon chains of biodiesel, with the largest increase in calorific value occurred in the blend with 10% soybean biodiesel (+ 8.70%). The viscosity of the blend with 10% castor bean biodiesel increased 23.8% and for the blends with 5% castor bean biodiesel and 10% soy biodiesel increased 15%. The flash point for the blends with 10% of soy biodiesel and of castor increased approximately 1 ° C, improving the security conditions in the fuel handling. The density extrapolated the ceiling of specified 1.42% for the blend with 10% castor biodiesel. This parameter is dependent on the amount of water present in the ethanol, which in this study if presented in the maximum, thus doing the density of blends exceed the limit. The electrical conductivity and the turbidity diagnosed homogeneous mixtures, without phase separation and increase in fuel lubricity.